Glycoprotein Targeted CAR-NK Cells for the Treatment of SARS-CoV-2 Infection - Christodoulou, Ilias; Rahnama, Ruyan; Ravich, Jonas W.; Seo, Jaesung; Zolov, Sergey N.; Marple, Andrew N.; Markovitz, David M.; Bonifant, Challice L. (Frontiers in Immunology, 2021)
H84T-Banana Lectin (BanLec) CAR-NK cells bind high mannose glycosites that decorate the SARS-CoV-2 envelope, thereby decreasing cellular infection in a model of SARS-CoV-2. H84T-BanLec CAR-NK cells are innate effector cells, activated by virus. This novel cellular agent is a promising therapeutic, capable of clearing circulating SARS-CoV-2 virus and infected cells. Banana Lectin (BanLec) binds high mannose glycans on viral envelopes, exerting an anti-viral effect. A point mutation (H84T) divorces BanLec mitogenicity from antiviral activity. SARS-CoV-2 contains high mannose glycosites in proximity to the receptor binding domain of the envelope Spike (S) protein. We designed a chimeric antigen receptor (CAR) that incorporates H84T-BanLec as the extracellular moiety. Our H84T-BanLec CAR was devised to specifically direct NK cell binding of SARS-CoV-2 envelope glycosites to promote viral clearance. The H84T-BanLec CAR was stably expressed at high density on primary human NK cells during two weeks of ex vivo expansion. H84T-BanLec CAR-NK cells reduced S-protein pseudotyped lentiviral infection of 293T cells expressing ACE2, the receptor for SARS-CoV-2. NK cells were activated to secrete inflammatory cytokines when in culture with virally infected cells. H84T-BanLec CAR-NK cells are a promising cell therapy for further testing against wild-type SARS-CoV-2 virus in models of SARS-CoV-2 infection. They may represent a viable off-the-shelf immunotherapy for patients suffering from COVID-19.